40.9k views
0 votes
A^-1/[a^-1 - b^-1] + a^-1/[a^-1 + b^-1]

User Mcsilvio
by
4.6k points

2 Answers

2 votes

Answer: Hopes it helps..... Your welcome

A^-1/[a^-1 - b^-1] + a^-1/[a^-1 + b^-1]-example-1
User Roudi
by
4.7k points
5 votes


(a^(-1))/(a^(-1)-b^(-1))+(a^(-1))/(a^(-1)+b^(-1))=a^(-1)\left((a^(-1)+b^(-1))/((a^(-1)-b^(-1))(a^(-1)+b^(-1)))+(a^(-1)-b^(-1))/((a^(-1)+b^(-1))(a^(-1)-b^(-1)))\right)


=a^(-1)\left(((a^(-1)+b^(-1))+(a^(-1)-b^(-1)))/(a^(-2)-b^(-2))\right)


=(2a^(-2))/(a^(-2)-b^(-2))


=(2b^2)/(b^2-a^2)

User Alyaxey
by
5.3k points